Prevalence and Determinants of Undernutrition in Under-Five Children in Urban Slums of Tripura, India - Manali Chakraborty; Saurav Basu; Suparna G. Jerath (Indian Journal of Community Medicine)
Background: We conducted this study to ascertain the prevalence of undernutrition in terms of stunting, wasting, and underweight for age and their determinants among under-five slum children in urban poor settlements in Tripura, India. Methods: This community-based cross-sectional study was conducted in a selected ward in the West District of Tripura from Jan to June 2023, including 353 children. The mothers of the respective children were interviewed regarding their sociodemographic status, household conditions, and child feeding practices. Results: The prevalence of stunting, underweight, and wasting was found to be 23.23% (95% confidence interval [CI]: 18.82%–27.63%), 23.23% (95% CI: 18.82%–27.63%), and 22.95 (95% CI: 18.56%–27.33%), respectively. The increasing age of the child and the lower maternal education were associated with increased odds of both wasting and being underweight. Children living in households using unclean fuel had nearly five times higher odds of stunting, 1.49 times higher odds of wasting, and 1.9 times higher odds of being underweight. Conclusion: The burden of undernutrition in under-five children in urban poor settlements was comparable to that in the general population of Tripura. Higher educational status of the mother and use of clean fuel (liquefied petroleum gas) were protective against adverse nutritional status (wasting and underweight) in the children.